2021
DOI: 10.3390/nu13124400
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intake and Dietary Inflammatory Potential in Current and Recovered Anorexia Nervosa

Abstract: Anorexia nervosa (AN) is characterised by disrupted and restrictive eating patterns. Recent investigations and meta-analyses have found altered concentrations of inflammatory markers in people with current AN. We aimed to assess nutrient intake in participants with current or recovered AN, as compared to healthy individuals, and explore group differences in dietary inflammatory potential as a possible explanation for the observed alterations in inflammatory markers. We recruited participants with current AN (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…Despite recovery from AN and weight gain to normal BMI the menstrual cycle does not resume in a considerable number of cases. Recent investigations have demonstrated alterations in inflammatory markers [30][31][32] as well as the gut microbiome and microbial metabolites [33,34] in this patient collective. Research in these areas may help uncover additional therapeutic options for patients with recovered AN in order to reinstate ovulatory cycles and conceive.…”
Section: Discussionmentioning
confidence: 82%
“…Despite recovery from AN and weight gain to normal BMI the menstrual cycle does not resume in a considerable number of cases. Recent investigations have demonstrated alterations in inflammatory markers [30][31][32] as well as the gut microbiome and microbial metabolites [33,34] in this patient collective. Research in these areas may help uncover additional therapeutic options for patients with recovered AN in order to reinstate ovulatory cycles and conceive.…”
Section: Discussionmentioning
confidence: 82%
“…The DII scores of individuals with impaired eating attitudes were high in different studies [16][17][18]. Again, in a different study, it was reported that inflammation was higher in individuals with a worse appetite according to the SNAQ results.…”
Section: Discussionmentioning
confidence: 90%
“…Eating attitude is defined as belief, thought, emotion and behaviors towards food [14] , although it is the basis of motor, cognitive, social and emotional development, but is considered a complex phenomenon regulated by environmental factors [15]. Eating attitudes also influence dietary inflammatory processes, for example, a 2021 study found that individuals with impaired eating attitudes had high DII scores [16]. Similarly, in studies on this subject, DII scores were found to be high in individuals with impaired eating attitudes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, altered expression levels of chemokine receptors may not be a consequence of nutrient deficiencies. Although women with AN consume less dietary zinc and cholesterol than HC, nutrient intake patterns do not contribute significantly to altered concentrations of immune markers in the blood in AN ( 90 ).…”
Section: Discussionmentioning
confidence: 99%